Description of Knowledge About Dental and Oral Hygiene Using Dental Wall Quiz Media (A Study Among Fifth Grade Students At SD Negeri 2 Balun,Turi, Lamongan) - Maulidiyah, Hafidho; Hadi, Sunomo; Prasetyowati, Silvia (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
Oral and dental hygiene is essential for overall health, particularly in primary school children, where inadequate oral care is commonly observed. Knowledge regarding oral and dental hygiene in this age group remains relatively low, adversely affecting This study aimed to address the issue of insufficient knowledge regarding oral and dental care among elementary school students. A descriptive research design was utilized, with 16 students participating as respondents. Data were collected using pre-test and post-test questionnaires. Scores were calculated by dividing the number of correct answers by the total number of questions, converted into percentages, and presented in tabular form to illustrate the students’ oral health status. The findings revealed that students’ knowledge was categorized as “low” before the counseling intervention and improved to the “good” category after the counseling.